Contribution of men and women to food crop production labour in Africa: information from COSCA - Enete, A.; Nweke, F.; Tollens, E. (2002)
It is widely reported that women provide the bulk of food production labour in Africa. Since efficient targeting of improved technologies demands an understanding of who is likely to use them, and new farm technologies have often been inappropriate for women's needs, this paper presents the relative contributions of men and women to food production labour in six major cassava-producing countries of Africa. The paper is based on farm-level information collected within the framework of the Collaborative Study of Cassava in Africa (COSCA). While the number of fields in which women provided more labour for each farm task increased consistently from the initial farm operations, such as land clearing and seedbed preparation, through sowing (planting) and weeding to the final farm operations such as harvesting and transportation, for which women provided more labour for the largest number of fields, the reverse was the case for men. The relative number of households where females provided more field labour than males was higher among female-headed households than among male-headed ones. Such households were characterized by a lower working age male/female ratio, and/or were engaged in tree crop production, which often absorbed male labour. Villages where females provided more field labour than males were more common in remote areas where access to markets was poor and population density sparse, or in countries where men had fled the villages because of political repression. Such villages were also more common among non-Muslim communities than among predominantly Muslim societies. On the whole, however, men contributed more labour in significantly more fields than women in most places. These observations suggest that it could be misleading to generalize that women are providing the bulk of food production labour across Africa. They provide clear evidence of gender division of labour on the farm, and help to explain gender bias in agricultural extension efforts in Africa. Recommendations that pre-harvest extension activities should be mainly directed at women have hardly been heeded. It is recommended that these activities should be targeted at both men and women, but more towards women where men have fled the villages for political reasons or for commercial ones such as poor market access opportunities.